Platelets in Neonatal Sepsis: Beyond Clotting, From Silent Players to Immune Orchestrators - Sokou, Rozeta; Lianou, Alexandra; Tsantes, Andreas G.; Petrou, Eleni; Bonovas, Stefanos; Nikolopoulos, Georgios; Tsantes, Argirios E.; Iacovidou, Nicoletta (Seminars in Thrombosis and Hemostasis, 2025)
Traditionally, platelet function has been defined in the context of their role in hemostasis and thrombus formation. In recent years, however, the concept of platelet function has expanded, as emerging evidence supports that platelets—despite their small size—serve as versatile and potent modulators in a wide range of biological processes, including immune responses. In the neonatal period, the immune response is immature and particularly susceptible to dysregulation. The distinct properties of neonatal platelets, compared with those of adults, may influence both the sensitivity and the magnitude of the inflammatory response. The aim of this review is to summarize current knowledge regarding the involvement of platelets in neonatal sepsis, to highlight the immunological and molecular characteristics implicated in this process, and to identify research gaps that limit the use of platelets as diagnostic and therapeutic targets in this particularly vulnerable population.
Keywords: platelet; neonates; immunothrombosis; thrombo-inflammation; thrombocytopenia